Analisa Hukum Islam dalam Meninggalkan Shalat Jum’at pada Masa Pandemi Corona Virus Disease 2019 (Covid-19) - Irdlon Sahil (Prodi Hukum Ekonomi Syariah (Muamalah), 2020)
This study discusses the legal status of leaving Friday prayers during the Corana Virus pandemic. Based on the source of Islamic law; al-Qur'an, hadith and ijma' ulama. In this study there are four conclusions, first, the scholars agreed that the law of Friday prayer is mandatory for people who are affected by the law of taklif and are in a state of pain, fear of illness, fear of life and property, rain, very cold or very hot weather and the outbreak of a disease such as coronavirus. Second, it is permissible not to perform Friday prayers if there is udzur in the way. It's part of the waiver in the goal of setting the law at a secondary level of need that turns into a primary need because the spread of this virus has been life-threatening. Third, it is obligatory to obey the leader, as long as the policy is not contrary to Islamic law. To measure the conformity of the leader's policy with sharia by referring to a benefit. Fourth, as long as the udzur syar'i is still struck, leaving Friday prayers is no limit.